2020
DOI: 10.24815/siele.v7i1.15359
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of Quizlet application towards students’ motivation in learning vocabulary

Abstract: Increasing motivation is necessary for students in learning English vocabulary. The higher motivation the students gain, the bigger success they achieve in mastering vocabulary. However, most students in senior high schools have less motivation in learning vocabulary, especially in memorizing them. Thus, the teachers need to discover appropriate media for increasing their motivation. Some applications can be used through the smartphone as the need for vocabulary learning. The purpose of this study is to invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
82
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(95 citation statements)
references
References 13 publications
8
82
0
5
Order By: Relevance
“…This result means that the research hypothesis was accepted, namely that there was an effect of using smartphone-based Quizlet on student interest in Accounting Education, Universitas PGRI Madiun. The study results supported the findings (Boyce, 2016;Hikmah, 2019;Hochberg et al, 2018;Setiawan & Wiedarti, 2020;Shyr et al, 2021;Wardana & Zakiah, 2019;Woodcock et al, 2012)as their built-in sensors allow many different measurements, but until now, there has been little research that studies this approach. Due to current interest in their development, it seems necessary to provide empirical evidence about potential effects of SETs by a well-controlled study.…”
Section: Resultssupporting
confidence: 84%
“…This result means that the research hypothesis was accepted, namely that there was an effect of using smartphone-based Quizlet on student interest in Accounting Education, Universitas PGRI Madiun. The study results supported the findings (Boyce, 2016;Hikmah, 2019;Hochberg et al, 2018;Setiawan & Wiedarti, 2020;Shyr et al, 2021;Wardana & Zakiah, 2019;Woodcock et al, 2012)as their built-in sensors allow many different measurements, but until now, there has been little research that studies this approach. Due to current interest in their development, it seems necessary to provide empirical evidence about potential effects of SETs by a well-controlled study.…”
Section: Resultssupporting
confidence: 84%
“…In an almost similar fashion, Chen (2012) reported that research has indicated that the use of technology may stimulate positive attitudes, for example, an increased level of interest, motivation, interaction, and language production. To be more specific, research by Setiawan and Wiedarti (2020) revealed that Quizlet application is effective in increasing students' motivation; moreover, Krishnapatria et al (2019) concluded that English language teaching using online Google Maps application can promote students' engagement and enhance their writing skill. Additionally, Stepp-Greany (2002) has discussed the advantages of technology for language learning and divided it into two sections, affective issues, and linguistics skills, as shown in Table 1.…”
Section: Technology In Teaching English As Second/foreign Language Lementioning
confidence: 99%
“…A number of studies (e.g. Chien, 2013;Chien, 2015;Kose, Cimen & Mede, 2016;Anjaniputra & Salsabila, 2018;Setiawan &Wiedarti, 2020) have focused on Quizlet and its merits for EFL learners' vocabulary learning and the findings of these studies were significantly positive. The following section discusses previous research in relation to learners' vocabulary performance and acquisition.…”
Section: Call and Mall In Language Teaching Vocabularymentioning
confidence: 99%